Career Preparation and the College Football Player - Muczko, John P.; Thompson, Mark A. (My University, 1994)
The lives of collegiate student-athletes are filled with needs: assistance in general scheduling/managing of campus activities, academic counseling, and career preparation. While it is generally accepted that all three areas are part of the challenges for academic athletic counselors, career preparation through a sound academic program is the fulfilling purpose of student-athletes. However, the number of graduating student athletes, particularly college football players, does not reflect this attitude. The purpose of this article was to present an overview of the college football player and information supporting the importance of strong academic athletic counseling.
Keywords: career development; football